PENGEMBANGAN MEDIA BOARD GAME EDUKATIF PADA MATA PELAJARAN PKN MATERI GOTONG ROYONG DI KELAS IV SEKOLAH DASAR (Sindoro: Cendikia Pendidikan, 2025)
This study aims to develop learning media about educational board games for PPKN subjects that focus on reciprocal cooperation material. With a research and development (FUE) approach using the Addie model, this study involves five stages: analysis, design, development, implementation and evaluation. The media aims to promote active student participation through interactive, entertaining games and related to elementary school properties. The results of the validation test indicate that this board game is suitable for use. This study contributes to the development of innovative learning media with the potential to increase motivation and understanding of the concept of reciprocal cooperation.